Assessing the progress and pitfalls of the Ministry of Environment, Forest, and Climate Change in achieving SDGs in Bangladesh (Bangladesh Journal of Public Administration, 2021)
The study strived to assess the performance of the Ministry of Environment, Forest, and Climate Change in achieving environmental sustainability in Bangladesh. The overarching pitfalls, shortcomings, and associated challenges were critically examined. The research used both primary and secondary data, which was collected following several research approaches. It was found that the Ministry is actively working to achieve 25 targets of SDGs. Nothing is mentioned about climate change in its mandates though it is nodal Ministry in climate adaptation and mitigation. Due to its ambiguous and viscous mandates, jurisdictional overlapping followed by the conflict of interests has been created in many other ministries and divisions. In SDGs mapping, this Ministry's role in achieving food security and responsible consumption have been downplayed. According to key informants' perception, it could not garner the community’s support in conservation initiatives. On the other hand, due to drawbacks in the legal framework, environmental justice could be ensured on an equal basis. No noticeable activities were observed that can achieve the targets 2020, agreed under the UN Convention on Biological Diversity (CBD), as part of the set of Aichi Biodiversity Targets. The Ministry could not establish any reliable database through which ecological, carbon, and green footprints can be measured. Correspondingly, Bangladesh Forest Research Institute cannot carry out need-based and world standard research activities. Institutional and legal reform is advocated to expedite the actions to achieve environmental sustainability. The study recommends enhancing the capacity of the Ministry.